KEBERHASILAN PENGEMBANGAN HUTAN KEMASYARAKATAN: KASUS DI KABUPATEN TANGGAMUS, PROVINSI LAMPUNG - Sylviani - Sylviani; Donny - Wicaksono; Niken - Sakuntaladewi (Jurnal Penelitian Sosial dan Ekonomi Kehutanan, 2020)
Community Forest (CF) development is the Ministry of Environment and Forestry’s policy to reduce deforestation, strengthen communities’ management rights, and reduce conflicts. This research aims to identify the determinant of CF success factors, including perceptions, community attitudes, potential benefits from CF, institutions, and ability of the community to overcome the problems in managing CF. This study was conducted in Bakti Makmur and Sumber Rejeki CFs, located in Kota Agung Utara Protection Forest Management Unit, Tanggamus District, Lampung Province. Perception analysis using Likert Scale method is to measure perceptions,attitudes, or opinions of a person or group regarding social phenomena. The community income was analyzed using quantitative methods with simple tabulations. The study shows that the community's perception of the CF development is high, both from their understanding, and readiness in implementing the CF program. The gross income of the CF farmer group is estimated at Rp24,760,000/ha/year. This study indicates that CF land can be used as a source of community income. Continuous guidance from the government to CF farmers is necessary in  facing challenges that continue to grow, while maintaining forest sustainability, improving forest cover.